2005
DOI: 10.1016/s0002-9440(10)62278-x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Smooth Muscle Cell-Like Phenotype in Marrow-Derived Cells among Regenerating Urinary Bladder Smooth Muscle Cells

Abstract: Tissue regeneration on acellular matrix grafts has great potential for therapeutic organ reconstruction. However, hollow organs such as the bladder require smooth muscle cell regeneration, the mechanisms of which are not well defined. We investigated the mechanisms by which bone marrow cells participate in smooth muscle formation during urinary bladder regeneration, using in vivo and in vitro model systems. In vivo bone marrow cells expressing green fluorescent protein were transplanted into lethally irradiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 47 publications
5
74
0
1
Order By: Relevance
“…Some authors suggest a major role for pluripotential stem cells in the graft cellular regeneration (19,20). On the other hand, other authors have demonstrated that muscle layer regeneration occurs by migration of dedifferentiated bladder SMC from the matrixbladder junction (15).…”
Section: A B Cmentioning
confidence: 99%
“…Some authors suggest a major role for pluripotential stem cells in the graft cellular regeneration (19,20). On the other hand, other authors have demonstrated that muscle layer regeneration occurs by migration of dedifferentiated bladder SMC from the matrixbladder junction (15).…”
Section: A B Cmentioning
confidence: 99%
“…Experimental data has demonstrated the utility of bone marrow (BM) cells in a bladder regenerative setting with data suggesting the phenotypic and physiological similarities between mesenchymal stem cells (MSCs) and bSMCs [7][8][9]. The characterization of a battery of contractile proteins shows that MSCs have a contractile protein profile similar to bSMCs [8].…”
Section: Introductionmentioning
confidence: 99%
“…Bladder tissue engineering using MSCs might show better results than by using differentiated cells. MSCs were shown to migrate to the bladder grafts and differentiate into smooth muscle cells (Kanematsu et al, 2005). These cells achieved fast repopulation of the grafts, which exhibited appropriate neural function and less fibrosis (Chung et al, 2005 (Zhang et al, 2005), and thus the use of MSCs may help to engineer a bladder when no bladder-derived cells are available.…”
Section: Urinary Tissues -Bladdermentioning
confidence: 99%